Leveraging Hadoop And Machine Learning Techniques In The Healthcare Industry - Dr. Priti Sadaria; Dr. Rupal Parekh (Educational Administration: Theory and Practice, 2024)
In the technological age, data is generated at very quick and processing as well as analysis these very big data is a not easy task. Conventional systems for managing databases are time consuming and are not able to analyze data fully. Healthcare industry have large quantity of data but it is lack of analysis so hidden pattern cannot be identify for prediction of any diseases. To overcome such issue, Big Data is used to handle and control large volume of data which may be either in structured or in unstructured form. The hidden pattern can be identified and prediction can be made about future condition. Hadoop MapReduce has the capability to facilitate healthcare industry to get better prediction of diseases and make faster and proper judgment for right future treatment of patient by analyzing healthcare data. Machine Learning algorithms can help to design predictive healthcare model for community wellness. I proposed system architecture to process and analyze data using Hadoop MapReduce with Machine Learning Techniques and ultimately it leads to prediction of diseases. As a result it increases life span as well as it leads to healthy life and reduce the rate of death by providing timely treatment.